Anti-Inflammatory Activity of Ferula assafoetida Oleo-Gum-Resin (Asafoetida) against TNF-α-Stimulated Human Umbilical Vein Endothelial Cells (HUVECs) - Leila Mobasheri; Mohsen Khorashadizadeh; Hossein Safarpour; Maryam Mohammadi; Gholamreza Anani Sarab; Vahid Reza Askari (Mediators of Inflammation)
Inflammation is the body’s biological reaction to endogenous and exogenous stimuli. Recent studies have demonstrated several anti-inflammatory properties of Ferula species. In this paper, we decided to study the anti-inflammatory effect of ethanolic extract of Ferula assafoetida oleo-gum-resin (asafoetida) against TNF-α-stimulated human umbilical vein endothelial cells (HUVECs). HUVECs were cultured in a flat-bottom plate and then treated with ethanolic extract of asafoetida (EEA, 0-500 μg/ml) and TNF-α (0-100 ng/ml) for 24 h. We used the MTT test to assess cell survival. In addition, the LC-MS analysis was performed to determine the active substances. HUVECs were pretreated with EEA and then induced by TNF-α. Intracellular reactive oxygen species (ROS) and adhesion of peripheral blood mononuclear cells (PBMCs) to HUVECs were evaluated with DCFH-DA and CFSE fluorescent probes, respectively. Gene expression of intercellular cell adhesion molecule-1 (ICAM-1), vascular cell adhesion molecule 1 (VCAM-1), and E-selectin and surface expression of ICAM-1 protein were measured using real-time PCR and flow cytometry methods, respectively. While TNF-α significantly increased intracellular ROS formation and PBMC adhesion to TNF-α-induced HUVECs, the pretreatment of HUVECs with EEA (125 and 250 μg/ml) significantly reduced the parameters. In addition, EEA pretreatment decreased TNF-α-induced mRNA expression of VCAM-1 and surface protein expression of ICAM-1 in the target cells. Taken together, the results indicated that EEA prevented ROS generation, triggered by TNF-α, and inhibited the expression of VCAM-1 and ICAM-1, leading to reduced PBMC adhesion. These findings suggest that EEA can probably have anti-inflammatory properties.